Scholarship for postgraduate studies (PhD) - Pantelides, Iakovos S. (My University, 2026)
Scholarship for postgraduate studies (PhD) in the field of Plant Pathology after scoring the second position in national examinations from the State Scholarships Foundation of Greece
Keywords: Education